PENGARUH KEPATUHAN MINUM OBAT TERHADAP OUTCOME PENGOBATAN TUBERKULOSIS PARU DI INDONESIA: TINJAUAN SISTEMATIS 2020–2025 - Chairil; Tri Siwi Kusumaningrum; Maswarni (Journal of Hospital Administration and Management (JHAM), 2026)
Background:Pulmonary tuberculosis (TB) remains a major public health problem in Indonesia, characterized by a high disease burden and persistent treatment failure. Adherence to anti-tuberculosis drug (ATD) therapy is a key determinant of successful treatment. This study aimed to analyze the relationship between medication adherence and treatment outcomes among patients with pulmonary tuberculosis in Indonesia through a systematic review. Methods: This study employed a systematic review based on the PRISMA 2020 guidelines. A literature search was conducted for articles published between January 2020 and March 2026 using several scientific databases. Eligible studies assessing medication adherence as the primary variable and treatment outcomes in patients with pulmonary tuberculosis were included and analyzed qualitatively. Results: A total of eight studies met the inclusion criteria. All included studies reported a significant association between medication adherence and treatment outcomes. Patients with high adherence were more likely to achieve successful treatment and recovery, whereas poor adherence was associated with an increased risk of treatment failure, loss to follow-up, relapse, and drug-resistant tuberculosis. Factors influencing medication adherence included patients’ knowledge and motivation, family support, the role of Treatment Supporters (PMO), and access to and quality of healthcare services. Conclusion: Medication adherence is significantly associated with treatment outcomes among patients with pulmonary tuberculosis in Indonesia. Therefore, interventions aimed at improving adherence through patient education, strengthening family support, optimizing the role of Treatment Supporters (PMO), and improving healthcare service quality should be prioritized to enhance the success of the national tuberculosis control program.